A Pimarane Diterpene and Cytotoxic Angucyclines from a Marine-Derived Micromonospora sp. in Vietnam’s East Sea - Mullowney, Michael W. (Mar Drugs, 2015)
A screening of our actinomycete fraction library against the NCI-60 SKOV3 human tumor cell line led to the isolation of isopimara-2-one-3-ol-8,15-diene (1), lagumycin B (2), dehydrorabelomycin (3), phenanthroviridone (4), and WS-5995 A (5). These secondary metabolites were produced by a Micromonospora sp. isolated from sediment collected off the Cát Bà peninsula in the East Sea of Vietnam. Compound 1 is a novel Δ(8,9)-pimarane diterpene, representing one of approximately 20 actinomycete-produced diterpenes reported to date, while compound 2 is an angucycline antibiotic that has yet to receive formal characterization. The structures of 1 and 2 were elucidated by combined NMR and MS analysis and the absolute configuration of 1 was assigned by analysis of NOESY NMR and CD spectroscopic data. Compounds 2–5 exhibited varying degrees of cytotoxicity against a panel of cancerous and non-cancerous cell lines. Overall, this study highlights our collaborative efforts to discover novel biologically active molecules from the large, underexplored, and biodiversity-rich waters of Vietnam’s East Sea.